Modelo de Gestión Administrativo - Financiero para las Industrias Paneleras de la Parroquia Malacatos, Cantón Loja - Avila Guayanay, Diana Micaela (2016)
This thesis work entitled "ADMINISTRATIVE - FINANCIAL MANAGEMENT MODEL FOR THE PANEL INDUSTRIES OF THE MALACATOS PARK, CANTÒN LOJA", has as main objective to serve as a base in the management of the human, material and financial resources that the panel industries have, Putting into consideration the stages of the administrative - financial process that entailed obtaining a good administration and improving its profitability. In order to comply with the purpose of the thesis work, a diagnosis was necessary to identify the external and internal factors present in the industries, to determine the legal basis with which they work and, in turn, to propose the rules to which they may be applicable, to identify the Administrative and financial processes that are developed within the industries and elaborate a model of administrative - financial management to strengthen the administration of its resources. The work considers a descriptive methodology and develops a proposal that contributes to solve the administrative - financial problems that the industries present, so the following methods are used: scientific, inductive, analytical, descriptive, synthetic and techniques such as interview, Observation and bibliographic review, which allowed the collection of information relevant to development. Each of the results obtained in the development of the investigative work is detailed below. A diagnosis of the current situation of the industries was made, for which the inductive method was used in order to corroborate the shortcomings that exist in the industries, interviews were applied to the owners and surveys to their workers through which some were evidenced Positive and negative factors that currently house the same, among which we have: Strengths: trained workers, quality control in the elaboration of the product, financing of their activities with their own resources. Weaknesses: poor administrative - financial management, lack of an administrative - financial management model. Opportunities: consumer interest in healthy products, government support to SMEs. Threats: decreased revenues of industries, decreased demand for the product, intensive competition in the market of production and marketing. Thus, analyzing the factors through the EFI and EFE matrix shows that the situation of the industries is not favorable because the weaknesses outweigh the internal strengths hindering their growth and development, and they do not take advantage of the opportunities existing in The medium as well as avoid threats. After the external and internal analysis the SWOT matrix was elaborated that was necessary to choose the strategies that contribute to the achievement of its objectives. In the elaboration of the legal regulations, it was determined through the interview that the industries do not have operating permits and lack a legal basis governing their operation; For which the form of constitution as a natural person required to carry out accounting, formal duties of the natural persons required to keep accounts, tax obligations and labor obligations to which they are subject have been considered. Regarding the administrative - financial procedures that are developed within the industries with the help of the survey and the observation was verified the absence of the administrative and financial process in the activities that are developed daily, the owners of the industries administer and manage their resources In an empirical way. Finally, for the elaboration of the administrative - financial management model, the descriptive method was used in each one of the phases of the proposed model; This model consists of an administrative, accounting and financial part according to the activities carried out by the industries. In the administrative part, the philosophy of industry, objectives, policies, structural and functional organization chart, function manual, process diagram, organizational forms, direction and control were taken into account by administrators. In the accounting part, we proposed accounting and financial policies, chart of accounts model, daily book, accounting entries, general ledger, worksheet, balance sheet and income statement. The financial part describes the types of financial analysis and the financial indexes that will allow to measure the performance of all the activities that are carried out in the industry. The conclusions and recommendations are based on the results of all thesis work emphasizing the most relevant points of the research. For this reason it is recommended to the owners of the industries to take into consideration the model presented, due to the importance that represents the administration in a company.